The Application Of Project Based Learning Towards Indonesian EFL Learners - Agustina, Ria Kamilah; Fajarina, Maskhurin; Daristin, Pipit Ertika (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
This study aims to justify the implementation of PBL to learning media projects and their activities in learning media Class at English Language Education Program Study of Hasyim Asy’ari University. Moreover, the paper undertakes a comprehensive analysis of pedagogical approaches and learning resources implemented in educational settings. The discussions suggest that project-based learning (PBL) fosters significant student engagement and promotes innovative instructional strategies. In Conclusion, this study offers actionable insights and practical strategies for EFL educators to enhance student learning outcomes through effective PBL implementation.